Uric acid in chronic kidney disease - Treviño Becerra, Alejandro; Iseki, Kunitoshi (Contributions to nephrology / series editor Claudio Ronco, 2018)
Hyperuricemia is often associated with life-style related disorders such as diabetes mellitus, hypertension, and dyslipidemia, which, in turn, are major causes of CKD. Improved management of hyperuricemia is thus expected to be beneficial for both the general population and CKD patients. This book presents new information on uric acid in tubular transport, early recognition of renal lesions, genetic predisposition, preeclampsia, metabolic syndrome, diabetes, high blood pressure in the young, and the relationship with vitamin D. Moreover, the relationship between AKI and uric acid, as well as the rejection of renal transplants due to hyperuricemia, are discussed. This publication will be of interest to both general practitioners and researchers working in the field of CKD. It provides new insights into renal damage caused by hyperuricemia and into prevention and treatment possibilities.